PENGEMBANGAN MEDIA PEMBELAJARAN AUDIO VISUAL CERITA BERGAMBAR BERBASIS KEARIFAN LOKAL PADA MATA PELAJARAN BAHASA INDONESIA KELAS II DI MADRASAH IBTIDAIYAH - Rachmawati, Rizky Dwi; Ilmi U, K, Linaria Arofatul; Mudayan, Arfian (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
This study aimed to develop an audio-visual learning media in the form of illustrated stories based on local wisdom for second-grade students in Indonesian language learning at Madrasah Ibtidaiyah. The research employed a Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The participants were 30 second-grade students at MI Muhammadiyah 1 Sukodadi. The instruments included expert validation sheets, student response questionnaires, and student activity questionnaires. The validation results indicated that the developed media was highly valid, with scores of 88% from media experts, 90% from design experts, and 85% from material experts. Limited and field trials showed very high levels of practicality, with scores of 81% and 88%, respectively. In conclusion, the developed audio-visual learning media is valid and practical for use in Indonesian language learning at the elementary level.